THE JIGSAW METHOD APPLICATION IN READING COMPREHENSION - Aprilianne, Ellen; Abas, Totoh Tauhidin; Puspitaloka, Nina (IKIP Siliwangi, 2024)
Reading comprehension is an essential basic skill in learning English. In junior high school, students often need help understanding descriptive text due to limited vocabulary and differences in language structure between English and Indonesian. This research aims to determine the application of the Jigsaw method in teaching reading comprehension of descriptive texts in grade 7 of junior high school. This research uses a qualitative approach with a case study design. The research participants were six 7th-grade students and 1 English teacher at a junior high school in Cikampek. Data collection was carried out through observations and interviews with teachers and students. The research results show that applying the Jigsaw method can help students understand the content of descriptive text. This research also identified several challenges in implementing the Jigsaw method, such as difficulty translating text from Indonesian to English and lack of coordination from group friends. However, the benefits of the Jigsaw method in learning reading comprehension of descriptive text show that students can understand the content of the text very well.